MHD Third Grade Thin Film Fluid Flow Over a Vertical Belt in the Presence of Thermal Radiation and Mass Transfer under Slip boundary conditions. - Nirmala P. Ratchagar, C. Surya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In the present paper, we have discussed the electrical conducting thin film flow of third grade fluid due to vertical belt in appearance of thermal radiation and mass transfer. The MHD and heat transfer analysis are taken into account. The non-linear conservative equations of presents problems are solved analytically under the appropriate boundary conditions by using traditional perturbation techniques. The results obtained are displayed graphically with respect to different pertinent parameters for flow velocity, temperature variation, profile of skin friction and concentration distribution.